PHILOSOPHICAL ANALYSIS OF GOOD AND EVIL - Olimjonova Nozima Foziljon qizi.; Salimov Bakhriddin Lutfullaevich. (Ustozlar uchun, 2025)
It is emphasized in the article that all spheres of society, all the processes taking place in it have a dialectical content, that the dialectical content and communication as a whole system apply equally to the society itself and to all spheres within it, whether it is the economic sphere or the political sphere, it cannot be dependent on dialectics.